Perspectives on Max Frisch - Bodine, Jay F.; Probst, Gerhard F. (Book collections on Project MUSE., 2015)
Max Frisch, with his countryman Friederich Diirrenmatt, shares the place of eminence in contemporary Swiss literature. Indeed, he ranks high among the recent leading writers in the German language. But, although several of his works -- novels and plays -- have been translated into English, he remains little known in America. In this collection of essays an international group of scholars provides a fresh introduction to this noted author. The three leading essays review Frisch's work in the forms he has used most extensively -- drama, narrative fiction, and the personal diary. The remaining nin.